Empirical Evidence on the Effects of Marginal Tax Rates on Income: The German Case - Hannes Schellhorn; Peter Gottfried (Institut für Angewandte Wirtschaftsforschung (IAW), 2004)
In 1990 the German personal income tax schedule underwent a major change. We interpret this reform as a ?natural experiment' and use a panel of individual income tax returns to analyze the response of income to changes in the individual tax rates. Our results suggest an average elasticity of taxable income with respect to the net-of-tax rate of around 0.4. Due to the detailed information the panel provides, we are not only able to distinguish between different levels of income but also between different types of income. We found very low elasticity estimates in the case of regular employment income, but values of up to 1.0 for business income and for high-income households.
Keywords: H24; H31; J29; 330; Einkommensteuer; Steuerreform; Steuerwirkung; Steueraufkommen; Elastizität; Schätzung; Deutschland